Physical therapy exerts sub-additive and suppressive effects on intracerebral neural stem cell implantation in a rat model of stroke. Issue 5 (May 2022) - Ghuman, Harmanvir; Perry, Nikhita; Grice, Lauren; Gerwig, Madeline; Moorhead, Jeffrey; Nitzsche, Franziska; Poplawsky, Alexander John; Ambrosio, Fabrisia; Modo, Michel
Intracerebral cell therapy (CT) is emerging as a new therapeutic paradigm for stroke. However, the impact of physical therapy (PT) on implanted cells and their ability to promote recovery remains poorly understood. To address this translational issue, a clinical-grade neural stem cell (NSC) line was implanted into peri-infarct tissue using MRI-defined injection sites, two weeks after stroke. PT in the form of aerobic exercise (AE) was administered 5 × per week post-implantation using a paradigm commonly applied in patients with stroke. A combined AE and CT exerted sub-additive therapeutic effects on sensory neglect, whereas AE suppressed CT effects on motor integration and grip strength. Behavioral testing emerged as a potentially major component for task integration. It is expected that this study will guide and inform the incorporation of PT in the design of clinical trials evaluating intraparenchymal NSCs implantation for stroke.